3ds Max: Revit Integration. - Crespi, Adam (linkedin.com, 2017)
Learn how to efficiently take a model from Autodesk Revit into Autodesk 3ds Max. Explore a streamlined workflow that optimizes Revit models for flexibility in rendering and design.